PEMBERDAYAAN EKONOMI KREATIF MASYARAKAT MELALUI MANAJEMEN BISNIS SYARIAH PENGOLAHAN MAKANAN TRADISIONAL DI DESA PAMIJAHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Yusuf Saefullah; Tubagus Rifqy Thantawi; Bayu Purnama Putra (SAHID EMPOWERMENT JOURNAL, 2021)
Abstract The creative economy can also be said to be the creation of added value based on ideas born from the creativity of human resources and based on the use of science, including cultural and technological heritage. Cibunian Village, Muara Legok Village has minimal business actors, the average population there only relies on farmers for their livelihood. The purpose of this service is to assist the community in Cibunian Village in processing traditional Kolang Kaling crackers as an effort to improve the community's economy. The implementation of this service uses the ESD (Education for Sustainable Development) method. ESD is a learning method to support sustainable development, which is a type of learning that provides awareness of an innovative and creative entrepreneurial spirit. The programs carried out include: 1) Counseling to improve the entrepreneurial spirit, 2) Training to process traditional Kolang Kaling Crackers, 3) Packaging/labeling training so that packaging becomes more attractive and markets products. The result of this service activity is the growing awareness of the Cibunian village community with an independent entrepreneurial spirit. Keywords: creative economy, traditional food, community empowerment